Physiology of shock and volume resuscitation - Kalla, M; Herring, N (Elsevier, 2013)
Haemorrhagic and severe hypovolaemic shock can be rapidly fatal unless identified and resuscitated quickly. Monitoring of haemodynamic and cellular end points is crucial in guiding treatment and improving outcomes. This review therefore focuses on the pathophysiology of hypovolaemic shock, volume resuscitation, haemostasis and approaches to management. Fluid resuscitation saves lives but considerable debate remains regarding the ideal fluid type and strategy to use. Blood transfusion is also a critical therapy in the shocked, bleeding patient with a lower threshold for transfusion being appropriate in the elderly patient with less physiological reserve. Reversal of anticoagulant medications and the administration of coagulation products should support both fluid and red cell therapy to counteract the multi-factorial coagulopathy that can accompany severe trauma, haemorrhage and shock. The aim is to stabilize the patient such that any interventional strategies (both percutaneous and surgical) can be considered for uncontrolled bleeding.